1999
DOI: 10.4314/ajfm.v7i2.24347
|View full text |Cite
|
Sign up to set email alerts
|

The Foreign Exchange Exposure of Japanese Multinational Corporations

Abstract: We find that about 25 percent of our sample of 171 Japanese multinationals' stock returns experienced economically significant positive exposure effects for the period January 1979 to December 1993. The extent to which a firm is exposed to exchange-rate f luctuations can be explained by the level of its export ratio and by variables that are proxies for its hedging needs. Highly leveraged firms, or firms with low liquidity, tend to have smaller exposures. Foreign exposure is found to increase with firm size. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
255
3
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(284 citation statements)
references
References 15 publications
21
255
3
5
Order By: Relevance
“…Whether it is favorable or unfavorable depends on the entire industrial structure within a country. Studies emphasizing on the impact of the exchange rate on stock price for Taiwan can be found in Wu (1997), Guo and Wu (1998) and Chiao, Hung, and Nwanna (2001); whereas Choi, Hiraki, and Takezawa (1998), He and Ng (1998), Doukas, Hall, and Lang (1999), Caporale, Pittis, and Spagnolo (2002), Elyasiani and Mansur (2005) and Homma, Tsutsui, and Benzion (2005) among others, studied the relationship between the exchange rate and stock price of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is favorable or unfavorable depends on the entire industrial structure within a country. Studies emphasizing on the impact of the exchange rate on stock price for Taiwan can be found in Wu (1997), Guo and Wu (1998) and Chiao, Hung, and Nwanna (2001); whereas Choi, Hiraki, and Takezawa (1998), He and Ng (1998), Doukas, Hall, and Lang (1999), Caporale, Pittis, and Spagnolo (2002), Elyasiani and Mansur (2005) and Homma, Tsutsui, and Benzion (2005) among others, studied the relationship between the exchange rate and stock price of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Bartov and Bodnar [24]; Choi and Prasad [25]; Jorion [26,27] found that firm value is insensitive to the exchange rate fluctuations. However the studies of He and Ng [28]; Bodnar and Gentry [29]; Booth and Rotenberg [30] found that exchange rate movement has a significant impact on the firm value. As said previously, the fact that large number of firms involving in the FX exposure management, we may say it has a positive impact on the firm value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, He and Ng (1998) investigated Japan 171 multinational firms there are about 25% firm"s stock returns significantly positively correlated to the foreign exchange exposures, themselves. And the effects are increasing as firm"s size increases.…”
Section: Wherementioning
confidence: 99%